Immune deficiency and autoimmunity in patients with CTLA‐4 (CD152) mutations. (21st July 2017) - Verma, N.; Burns, S. O.; Walker, L. S. K.; Sansom, D. M.
Summary: Immune deficiency disorders are a heterogeneous group of diseases of variable genetic aetiology. While the hallmark of immunodeficiency is susceptibility to infection, it is increasingly clear that autoimmunity is prevalent, suggestive of a more general immune dysregulation in some cases. With the increasing use of genetic technologies, the underlying causes of immune dysregulation are beginning to emerge. Here we provide a review of the heterozygous mutations found in the immune checkpoint protein CTLA‐4, identified in cases of common variable immunodeficiency disorders (CVID) with accompanying autoimmunity. Study of these mutations provides insights into the biology of CTLA‐4 as well as suggesting approaches for rational treatment of these patients. Abstract : Heterozygous mutations in the CTLA‐4 gene cause immune deficiency and autoimmunity.